Analisis Relasi Hiponimi dan Hiperonimi dalam Artikel Kesehatan di Kompas.Id - Dwi Praptiwi; Dian Nurul Fitra; Fatmawati Fatmawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the relationship between hyponymy and hyperonymy in health articles published in Kompas.id from January to March 2025. The hyponymy-hyperonymy relationship is a relationship of meaning between general terms (hyperonyms) and specific terms (hyponyms) that plays an important role in arranging information hierarchically and systematically. This study uses a descriptive qualitative method with data collection techniques of reading, listening, and taking notes. Data were analyzed by identifying words that have a relationship of meaning, classifying them into hyponymy-hyperonymy, and analyzing the function of their use in sentences. The results of the study show that the use of hyponymy and hyperonymy relationships in health articles helps clarify information, facilitates reader understanding, and builds text cohesion and coherence. This relationship is used both for generalization of meaning and specification of meaning in conveying health information to the wider community.